APPLICATION TO IDENTIFY DISEASE BASED ON SYMPTOMS USING PHP - Dita Kurniasih; Diyah Ruri Irawati, Skom, MMSI (Jurnal Sistem Informasi, 2005)
Scientific writing is about an application to identify the type of disease based onsymptoms, which the author tries to present how to identify the disease using acomputer system. This application is made to meet the needs of patients or peoplewho need them.In this scientific writing, Application To Identify Disease Symptoms Based createdusing PHP programming language or PHP Hypertext Preprocessor is a form oflanguage scripts that are placed on the server and processed in the process. The resultis sent to the client, where using the browser. In particular, PHP is designed to createdynamic web, meaning that it can form a view based on current demand.